Some aspects of the investment attractiveness of the Visegrad Group countries - P. Bielik; E. Horská; M. Dziembala (Agricultural Economics (AGRICECON), 2006)
The article stresses the importance of analysing the inflow of foreign direct investments to the countries of the Visegrad Group. In this context, what is shown is the attractiveness of the CEE countries, including the Visegrad Group, in terms of the FDI location; and there are also other factors depicted, which determine the attractiveness of regions for foreign investors. The EU accession gave the Visegrad Group countries new opportunities to attract FDI; the point is to take advantage of these opportunities. Actions at both national and regional level are constantly needed in order to enhance the location attractiveness, since the VG countries need capital to modernize their economies. The quality of the investments attracted is also crucial, as the "modern" ones will create stable bases for the economy modernization and for building of a sustainable competitive advantage.